Golgi-restored vesicular replenishment retards bone aging and empowers aging bone regeneration - Peisheng Liu; Hao Guo; Xiaoyao Huang; Anqi Liu; Ting Zhu; Chenxi Zheng; Fei Fu; Kaichao Zhang; Shijie Li; Xinyan Luo; Jiongyi Tian; Yan Jin; et al. (Bone Research)
Abstract Healthy aging is a common goal for humanity and society, and one key to achieving it is the rejuvenation of senescent resident stem cells and empowerment of aging organ regeneration. However, the mechanistic understandings of stem cell senescence and the potential strategies to counteract it remain elusive. Here, we reveal that the aging bone microenvironment impairs the Golgi apparatus thus diminishing mesenchymal stem cell (MSC) function and regeneration. Interestingly, replenishment of cell aggregates-derived extracellular vesicles (CA-EVs) rescues Golgi dysfunction and empowers senescent MSCs through the Golgi regulatory protein Syntaxin 5. Importantly, in vivo administration of CA-EVs significantly enhanced the bone defect repair rate and improved bone mass in aging mice, suggesting their therapeutic value for treating age-related osteoporosis and promoting bone regeneration. Collectively, our findings provide insights into Golgi regulation in stem cell senescence and bone aging, which further highlight CA-EVs as a potential rejuvenative approach for aging bone regeneration.